Comparative genomic profiling of SLC26A4-expressing cells in the inner ear and other organs - Keiji Honda; Akimasa Kajino; Takeshi Tsutsumi (PLoS ONE, 2025)
Pendred syndrome and autosomal recessive non-syndromic hearing loss, type 4 (DFNB4), are associated with mutations in SLC26A4 that encodes the anion transporter SLC26A4 (pendrin). SLC26A4 is expressed in mitochondria-rich cells of the endolymphatic sac, spindle and root cells in the cochlear lateral wall, transitional cells in the vestibular organs, follicular cells in the thyroid, and type B intercalated cells in the kidney. This study aimed to assess the gene profiles of murine Slc26a4-expressing cells to better understand the regulatory mechanisms and functions of SLC26A4. Publicly available murine single-cell or single-nucleus RNA-sequencing (RNA-seq) datasets from the endolymphatic sac, cochlear lateral wall, utricle, kidney, airway, epididymis, and salivary glands were collected. After quality control, principal component analysis and clustering, distinct cell populations were identified, and differentially expressed genes (DEGs) were analyzed. The datasets were integrated for comparison across multiple tissues and organs. The results revealed no shared genetic profile among inner ear Slc26a4-expressing cells, with Slc26a4 being the only shared DEG, suggesting that regulatory genes may include low expression transcripts, splicing variants, or long non-coding RNAs undetectable by single-cell analysis. Comparative analysis within the ionocyte family identified distinct DEGs such as Insrr and Hmx2 in Slc26a4-expressing cells from the endolymphatic sac and kidneys, potentially significant in ion homeostasis and SLC26A4 regulation. This study highlights the specificity and complexity of SLC26A4 expression and highlights the challenges and limitations of single-cell analysis. Future research should address regulatory elements such as low-expression genes, splicing variants, and non-coding RNAs to enhance our understanding of SLC26A4 regulation across various cellular contexts.